Evaluating the forensic importance of glottal source features through the voice analysis of twins and non-twin siblings - San Segundo, Eugenia; Gómez-Vilda, Pedro (Language and Law / Linguagem e Direito, 2017)
In this study we have analyzed 853 tokens of the vowel filler [e:], extracted from spontaneous speech fragments of 54 male Spanish speakers (NorthCentral Peninsular variety), each one recorded on two separate sessions. The speakers — to be compared in a pairwise fashion – were divided in four groups: 24 monozygotic (MZ) twins, 10 dizygotic (DZ) twins, 8 non-twin brothers and 12 unrelated speakers. From the extracted vowel fillers, considered long enough for a glottal analysis (around 160 milliseconds), a vector of 68 glottal parameters was created. Our hypothesis that higher similarity values would be found in the intra-pair comparison of MZ twins than in DZ twins, brothers or unrelated speakers was confirmed, which suggests that the glottal parameters under investigation are genetically influenced. This finding seems of great forensic importance, as a phonetic parameter is considered forensically robust provided that it exhibits large between-speaker variation while it remains as consistent as possible for each speaker (i.e. small within-speaker variation).